How the inaccessibility index can improve transport planning and investment - Floridea Di Ciommo (Organisation for Economic Co-operation and Development (OECD), International Transport Forum, 2018)
Within the equity in transport framework, this paper  provides an overview on the rationale of using the needs-based approach for transport planning assessment. The paper is structured into three parts. First, the presentation of the needs-based approach using the inaccessibility index. Second, the interpretation of the index through the case of Barcelona. The focus will be on how the inaccessibility index allows us to capture relevant information on the satisfied mobility needs of different population groups (particularly for vulnerable groups of the population) through different transport modes. Finally, the potential incorporation into transport planning/assessment frameworks. This section discusses the ways in which the index could be implemented in two different contexts: ex-ante infrastructure evaluation and assessment of a deprived geographic area for transport strategic planning.
Keywords: 330